Different habitats within a region contain evolutionary heritage from different epochs depending on the abiotic environment. Issue 3 (11th December 2015) - Bartish, Igor V.; Ozinga, Wim A.; Bartish, Mark I.; Wamelink, G. W. Wieger; Hennekens, Stephan M.; Prinzing, Andreas
Abstract: Aim: Biodiversity hot‐spots are regions containing evolutionary heritage from ancient or recent geological epochs, i.e. evolutionary 'museums' or 'cradles', respectively. We hypothesize that: (1) there are also 'museums' and 'cradles' within regions – some species pools of particular habitat types contain angiosperm (flowering plants) lineages from ancient geological epochs, others from recent epochs; (2) habitat‐specific abiotic factors control the number of angiosperm lineages from a given epoch contained in a given habitat species pool. Location: The flora of the Netherlands. Methods: We studied the world's largest vegetation‐plot database and a new, uniquely resolved dated angiosperm phylogeny available for the Netherlands. We characterized species pools of habitat types by a novel concept: epoch‐specific lineage diversities. Results: We found that species pools of most habitat types were characterized by over‐ or underrepresentation of lineages from at least one epoch, dating back to the origin of angiosperms. These patterns are not captured by mean lineage ages. Abiotic environments explained on average 56% and up to 75% of the variance in the number of lineages per epoch, but with opposing effects of the same factor for different epochs. Specifically, warm and dry habitats tend to contain lineages dating back to warm and dry epochs. Identifying lineages from sets of random time intervals rather than from a set of geological epochs significantly reduced relationships with the environment. Main conclusions: Within a region, habitat types differ significantly in the evolutionary heritage they contain from different geological epochs, and these differences are controlled by the environment.